2021
DOI: 10.3390/e23080928
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Instrumental Variables in Causal Inference Based on Independence of Cause and Mechanism

Abstract: Causal inference methods based on conditional independence construct Markov equivalent graphs and cannot be applied to bivariate cases. The approaches based on independence of cause and mechanism state, on the contrary, that causal discovery can be inferred for two observations. In our contribution, we pose a challenge to reconcile these two research directions. We study the role of latent variables such as latent instrumental variables and hidden common causes in the causal graphical structures. We show that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Failing to adjust such a confounder will lead to spurious association between the explanatory variable and the outcome. Analysis of instrumental variables (IV) has gained popularity in causal inference, such as investigating causal graphical structures [ 1 , 2 ] and controlling for unmeasured confounding [ 3 , 4 ]. An instrument is a variable that is correlated with the explanatory variable but not associated with any unmeasured confounders.…”
Section: Introductionmentioning
confidence: 99%
“…Failing to adjust such a confounder will lead to spurious association between the explanatory variable and the outcome. Analysis of instrumental variables (IV) has gained popularity in causal inference, such as investigating causal graphical structures [ 1 , 2 ] and controlling for unmeasured confounding [ 3 , 4 ]. An instrument is a variable that is correlated with the explanatory variable but not associated with any unmeasured confounders.…”
Section: Introductionmentioning
confidence: 99%
“…Instrumental variable in causal inference. Papers [ 1 , 2 , 3 ] investigate models using instrumental variable in causal inference. Paper [ 1 ] deals with the challenge to reconcile the approaches to causal inference based on independence of cause and mechanism, and approaches based on conditional independence.…”
mentioning
confidence: 99%
“…Papers [ 1 , 2 , 3 ] investigate models using instrumental variable in causal inference. Paper [ 1 ] deals with the challenge to reconcile the approaches to causal inference based on independence of cause and mechanism, and approaches based on conditional independence. It is shown that methods based on the independence of cause and mechanism indirectly contain traces of the existence of hidden instrumental variables (IV).…”
mentioning
confidence: 99%